A New Subclass of Analytic Functions Related to Mittag-Leffler Type Poisson Distribution Series. (1st February 2021) - Alessa, Nazek; Venkateswarlu, B.; Reddy, P. Thirupathi; Loganathan, K.; Tamilvanan, K.
Abstract : The object of this work is to an innovation of a class k − U S T s ℏ, υ, τ, ι, ς in Y with negative coefficients, further determining coefficient estimates, neighborhoods, partial sums, convexity, and compactness of this specified class.